Impact and cost-effectiveness of water, sanitation, hygiene, and health education interventions in the control and elimination of soil-transmitted helminthiasis: A scoping review - Collins Okoyo; Michael Odhiambo; Geofrey Chepchieng; John Kioko; Britney Nyanchama; Michelle Anjela; Charles Mwandawiro; Mark Minnery (PLOS Neglected Tropical Diseases, 2026)
Background Soil-transmitted helminthiasis (STH) remains a major public health problem in many low- and middle-income countries (LMICs) despite widespread implementation of mass drug administration (MDA). Rapid reinfection after treatment highlights the limitations of MDA approaches and underscores the need for complementary interventions. Water, sanitation, hygiene, and health education (WASH) interventions are widely promoted as essential components of integrated STH control strategies. However, evidence on WASH impact and cost-effectiveness remains fragmented and is poorly synthesized. This scoping review aimed to systematically map and summarize the evidence on the impact and cost-effectiveness of WASH interventions for STH control and elimination. Methods Following Arksey and O’Malley’s framework and the Preferred Reporting Items for Systematic reviews and Meta-Analysis extension for Scoping Reviews (PRISMA-ScR) guidelines, we conducted a scoping review of peer-reviewed and grey literature with no date restrictions. We searched PubMed and Google Scholar for papers that met our inclusion criteria. Studies assessing the impact and/or cost-effectiveness of WASH interventions, alone or integrated with MDA, on STH outcomes were included. Principal findings Sixteen studies, predominantly from LMICs, met the inclusion criteria, with Kenya contributing the largest number. Findings showed that combining WASH interventions with MDA led to greater reductions in reinfection with Ascaris lumbricoides than MDA alone, particularly in school- and community-based programs. However, behavioural improvements alone were insufficient without supporting infrastructure, and their effects on other helminths were inconsistent. Notably, only one study conducted a formal cost-effectiveness analysis of WASH interventions, revealing a critical gap in economic evidence. Conclusion Integrating WASH interventions with MDA can enhance STH control outcomes, particularly for A. lumbricoides, but the lack of robust economic evaluations limits informed policy and investment decisions. Future research should prioritize cost-effectiveness analyses and long-term assessments of integrated WASH strategies to support sustainable STH elimination efforts.